Assessment of Students’ Safety and Environmental Activities for Teaching Milling Machine Maintenance in Technical Colleges - UDOINYANG, Dr. NATHAN; Johnson Abor, Dr. ITEKU; Daniel , Dr. Reuben (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2026)
The increasing complexity of industrial machinery necessitates a standardized approach to safety and maintenance training within technical education. Objective: This study aimed to assess students' activities regarding safety measures for inclusion in a capacity-building module designed for teaching milling machine maintenance in technical colleges. Methodology: A descriptive survey research design was adopted, gathering data from technical educators and workshop instructors in Delta State. The sample comprised 70 respondents, including 26 technical teachers and 44 workshop instructors, drawn from four government technical colleges. Data collection was facilitated through structured questionnaires, while mean, standard deviation, and t-test statistics were employed for comprehensive data analysis. Findings: The results revealed that both technical teachers and workshop instructors strongly agreed that the identified safety measures, instructional materials, and methodologies were highly appropriate for inclusion in the developed module. Furthermore, no significant differences were found in the responses of the two groups, underscoring a professional consensus on the variables required to enhance effective teaching and safe practices. Conclusion & Recommendations: The study concludes that the developed capacity-building module serves as a critical tool for improving teaching and learning outcomes in milling machine maintenance. It is recommended that technical teachers strictly adopt these safety measures in their instructional activities. Additionally, curriculum planners and the National Board for Technical Education (NBTE) should integrate the module into formal programs, supported by government and administrative resources to ensure successful implementation.